2014
DOI: 10.2176/nmc.st.2013-0377
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Stabilization for Degenerative Spondylolisthesis and Lumbar Spinal Instability

Abstract: Lumbar interbody fusion is a widely accepted surgical procedure for patients with lumbar degenerative spondylolisthesis and lumbar spinal instability in the active age group. However, in elderly patients, it is often questionable whether it is truly necessary to construct rigid fixation for a short period of time. In recent years, we have been occasionally performing posterior dynamic stabilization in elderly patients with such lumbar disorders. Posterior dynamic stabilization was performed in 12 patients (6 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Moreover, dynamic stabilization showed favorable outcomes in older patients with degenerative spondylolisthesis, with better fusion rates in fusion surgery using the dynamic stabilization system than in conventional fusion systems [27]. This finding supported our own system.…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, dynamic stabilization showed favorable outcomes in older patients with degenerative spondylolisthesis, with better fusion rates in fusion surgery using the dynamic stabilization system than in conventional fusion systems [27]. This finding supported our own system.…”
Section: Discussionsupporting
confidence: 84%
“…However, it was reported that pseudarthrosis may develop in 5-25% of patients who underwent PLF and 50% of patients with pseudarthrosis may be asymptomatic (23). Moreover, it was reported that short-term results of dynamic systems which have been started to be used in degenerative spondylolisthesis in recent times were successful and similar to the results of fixation and PLF (24,25). We think that short-term results of studies related to dynamic system may explain that patients develop pseudarthrosis but are asymptomatic patients.This is because dynamic fixation systems allow partial movement in the sagittal plane although they do not create instability as in the preoperative period.…”
Section: Discussionmentioning
confidence: 96%
“…As a concept of ADS, the share of increased load at UAD level is expected. 9) We therefore tolerate long-term final fusion at the dynamically stabilized level, but patients more than 50 years who undergo ADS will receive benefits from delayed ASD compared to those who undergo PLIF.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, we reported the short- to mid-term clinical and radiological outcomes about our previous dynamic stabilization. 9) In that report, as a concept of dynamization, two types of dynamization were introduced as dynamic stabilization mechanisms for different types of pathophysiology. One is dynamic stabilization that allows perpendicular movement for lumbar degenerative spondylolisthesis, and the other is that allowing sagittal movement for lumbar disc herniation in which postoperative instability is a concern because of an apparent vacuum phenomenon.…”
Section: Introductionmentioning
confidence: 99%